Feed Processing and Feed Formulation of Compound Feeds for sheep fattening in Ethiopia: A Training Report - Ekule, Muluken; Rudiger, Udo; Wamatu, Jane (International Center for Agricultural Research in the Dry Areas, 2023)
The training targeted youth and women sheep fattening groups, aiming to enhance their knowledge and skills in optimizing feed management practices. ICARDA partnered with the National Agricultural Research Centers of Areka, Bonga, and Debre Berhan to deliver the training sessions. The objective of the trainings was to equip participants with the necessary expertise to formulate balanced sheep diets and efficiently process feed, thereby improving sheep productivity and promoting sustainable livestock feeding practices.